A survey of various intelligent home applications using IoT and intelligent controllers - Mustafa Asaad Omran; Wasaan Kadhim Saad; Bashar Jabbar Hamza; Ahmed Fahem Al-baghdadi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The tremendous development in technology used in our daily life was one of the most important incentives for researchers to add technology that is easy to use and useful in human life, an example internet of things (IoT) and systems of intelligence used in various fields. This article provides an overview of the smart home (SH) study of the Internet of Things as smart homes (SHs) have attracted great interest with communication technology advancements. The intelligent home is an Internet of Things technology that allows the monitoring and control of devices via the Internet using a home automation system (HAS). Followed by the justification for choosing the smart home and smart home engineering, and what are the most used communication protocols for smart homes, whether wired or wireless.